Prospects of cultivation technologies for restoration of population of plants tau-sagyz (Scorzonera tau-saghyz Lipsch. et Bosse) in Karatausky State Natural Reserve (Eurasian Journal of Ecology, 2016)
In the article is resulted the short historical review of a condition and prospect of restoration of a rare unical species of a rubber-bearing plant Tau-sagyz. It’s presented introduction techniques in culture and theorganizations of nurseries. Have been described the prospects of the use biotechnological methods (micro propagation) for obtain of new lines of tau-sagyz with the high content of rubber.
Keywords: tau-sagyz (Scorzonera tau-saghyz); seeds; rubber; micropropagation